Comparison of Spermatozoa Quality of Masamo Catfish (Clarias sp.) In Different Extender During Short-Term Preservation - Savitri, Dhea Auryn; Ducha, Nur (LenteraBio : Berkala Ilmiah Biologi, 2022)
The community’s need for catfish consumption is very high, so it is necessary to provide enough semen. An effort to provide semen is diluting the semen so that more eggs are fertilized. The study aimed to determine the best extender in maintaining spermatozoa quality of Masamo catfish during short-term preservation. This study used a Completely Randomized Design (CRD) with four treatments and five repetitions, namely without extender (TP), Ginsburg Fish Ringer (GF), 0.9% NaCl (NA) and Immobilizing Saad (IS). Fresh semen was diluted at 1:5 ratio with different extenders. Motility and viability of Masamo catfish spermatozoa were measured. Data were analyzed with the Kolmogorov-Smirnov test and continued with the one-way ANOVA and Duncan’s tests. The results showed that the Immobilizing Saad media was able to maintain the average percentage of motility during 0, 1, 24 and 48 hours storage are 88.00% ± 3.71; 87.00% ± 3.26; 78.50% ± 3.79; 12.50% ± 3.54 respectively and average viability percentages were 91.29% ± 1.55, 89.19% ± 2.18, 81.95% ± 1.99, 58.93% ± 3.01 respectively. Based on the research, it can concluded that Immobilizing Saad extender is the best extender to maintain motility and viability of Masamo catfish spermatozoa during short-term preservation.